Wanprestasi Dalam Perjanjian Antara Taylor Mahirah Gorden Dengan Pemilik Pakaian - Rina Arjukni; Ramziati R; Arnita A (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
Default means less performance either or does not fulfill this obligation as which has been agreed. No only it can also be meant the absence of something Achievement. and if there is a default, icertainly infringement of in law interest, iinterest which is regulated and protected by law - the debtor, even though-has been declared negligent, still negligent to fulfill the commitment, or if something which must be given or do only in a time which has been determined. The type of study used in in this study is a juridical empirical study. The data sources for this research are primary data and secondary data. This research is classified as research with qualitative data types, namely by managing primary data sourced from Taylor Mahirah Gorden. The results of the research from this paper indicate that: 1) What are the causes for the occurrence of default in the agreement between the sewing owner and the tailor. 2) Efforts to resolve non- performance that were carried out by business sewing services clothes Taylor Mahirah curtains.